Effects of sacubitril/valsartan on life quality in chronic heart failure: A systematic review and meta-analysis of randomized controlled trials - Song, Yinyin; Zhao, Zinan; Zhang, Jingwen; Zhao, Fei; Jin, Pengfei (Frontiers in Cardiovascular Medicine, 2022)
Aims: Sacubitril/valsartan has been demonstrated to have cardiovascular benefits in patients with chronic heart failure (CHF). We aimed to conduct a meta-analysis of its effects on life quality in patients with CHF, in comparison with the renin-angiotensin-aldosterone system inhibitor. Methods: PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov were searched from inception through March 2022 for all relevant randomized controlled trials assessing the impact of sacubitril/valsartan and angiotensin-converting enzyme inhibitor/angiotensin receptor blocker (ACEI/ARB) on health-related quality of life (HRQoL) in patients with CHF. Two reviewers independently conducted study selection, data extraction, and assessment of bias and quality of evidence. Review Manager 5.3 software was used for meta-analysis. Results: We included 10 clinical studies involving 10426 patients with heart failure with reduced ejection fraction (HFrEF) and 7689 patients with heart failure with preserved ejection fraction (HFpEF). Meta-analysis results showed that, in terms of the primary outcome, the sacubitril/valsartan group was superior than the ACEI/ARB group in improving HRQoL of HFrEF, and the difference was statistically significant (SMD 1.26; 95% CI: 0.14, 2.37; p = 0.03) between the two groups, while there was no significant difference between the two groups in HFpEF (SMD 0.37; 95% CI: −0.35, 1.09; p = 0.32). The effect of sacubitril/valsartan on the secondary outcome of the minimal important improvement rate of HRQoL in HFrEF was consistent with the primary outcome, while the effect in HFpEF was not clear. The descriptive analysis of individual studies showed that there was no significant difference in the improvement of 6-minute walk distance between the two groups. Conclusion: Sacubitril/valsartan is beneficial to improve HRQoL outcome in patients with HFrEF with high quality of evidence. Compared with ACEI/ARB, sacubitril/valsartan was more effective. While in patients with HFpEF, this improvement was similar between the two groups.